25 April 1974 and a clandestine network of naval officers - Oliveira, L. T. de. (Portuguese Journal of Social Science, 2025)
The coup of the ‘Movimento das Forças Armadas’ (MFA; ‘Armed Forces Movement’) was based on low-ranking officers in the army. As it is well known, the conspiracy and the bulk of the action on 25 April was carried out mainly by one of the military branches, the army, while the others, the air force and the navy, had modest operational participation. In the case of the navy, the modesty of its place in the conspiracy and the coup itself can be contrasted with its strong role in the later revolutionary period (1974–76). This article results from broader research on the structuring, course and role of a political organization of military (naval) officers, in the context of a Transition to Democracy through revolutionary means. The article focuses on the navy’s MFA in 25 April and the previous Organização Clandestina de Oficiais da Armada (OCOA; Clandestine Organization of Naval Officers), led by Martins Guerreiro, Almada Contreiras and Miguel Judas. The article will try to contextualize what was the OCOM, which role it played in the conspiracy, on 25 April 1974 and in the days immediately following. One can perceive the weight of the OCOM in those days through their attention to the Programme of the MFA and their intervention on the ground. Additionally, their contribution was decisive to the aesthetics of 25 April and the symbolic storming of the ‘Bastilles’, an unequivocal sign of the end of the New State, an open door to many other changes and movements.